Association Between Globulin and Diabetic Nephropathy in Type2 Diabetes Mellitus Patients: A Cross-Sectional Study - Wang, Jian; Liu, Fang; Kong, Rongzhen; Han, Xiuxia (Frontiers in Endocrinology, 2022)
Background: The living standards of people worldwide have been greatly improved with the development of economy, and the incidence of diabetes is also increasing. Many patients also develop other complications that reduce their quality of life. Diabetic nephropathy is a common complication of type 2 diabetes. Realizing relevant factors of diabetic nephropathy is greatly significance to control the occurrence of diabetic nephropathy and improve their life quality. Data and Methods: Data from 2009 to 2018 were downloaded from NHANES. The relationship between globulin (GLB) and diabetic nephropathy(DN) was observed by curve fitting graph. Four logistic regression models were used to controll the potential confounding factors. Subgroup analysis was carried out to test the stability of results. Results: We found that GLB was positively correlated with the occurrence of DN after controlling for potential confounders. Higher GLB was associated with an increased risk of diabetic nephropathy ( odds ratio(OR), 1.10; 95% confidence interval (CI), 1.07-1.13, P < 0.001) . Conclusions: In this cross-sectional study, GLB was significant positively correlated with the occurrence of DN in patients with type 2diabetes mellitus.